ANALYSIS OF POSTER REDESIGN EFFECTIVENESS AS A PROMOTIONAL MEDIA - Utami, Athika Dwi Wiji (Jurusan Seni Rupa Fakultas Bahasa dan Seni, 2020)
This study aims: (1) to analyze the effectiveness of posters before and after being redesigned as a promotional media from the aspects of the EPIC Model; and (2) comparing two paired samples in the form of the same sample group with two different measurements in assessing the effectiveness of posters before and after redesign as promotional media. This research approach is descriptive quantitative and comparative. The sample for this test was 60 respondents from students of the Visual Communication Design study program at UNUSIDA Class of 2017 to 2019. The research sampling technique was random sampling. The data were analyzed using the EPIC Model analysis method through distributing Likert scale questionnaires. In addition, a paired comparison test was conducted using the Paired t test with the help of SPSS. The results of the study included: (1) poster media before redesign was declared quite effective based on the dimensions of Empathy, Persuasion, Impact, and Communication with a value of 3,2; (2) poster media after redesign is declared effective based on the dimensions of Empathy, Persuasion, Impact, and Communication with a value of 4,1; (3) based on the four dimensions of Empathy, Persuasion, Impact, and Communication, there is an increase in the value before redesign from 3,2 to 4,1 after the redesign; and (4) media effectiveness can be increased through the use before and after poster redesign